Estimating the Effect of Personality on Male-Female Earnings - Gerrit Mueller; Erik Plug (Tinbergen Institute, 2004)
The authors adopt the Five-Factor Model of personality structure to explore how personalityaffected the earnings of a large group of men and women who graduated from Wisconsin highschools in 1957 and were re-interviewed in 1992. All five basic traits–extroversion, agreeableness,conscientiousness, neuroticism, and openness to experience–had statistically significant positiveor negative earnings effects, and together they appear to have had effects comparable to those commonlyfound for cognitive ability. Among men, substantial earnings advantages were associatedwith antagonism (the obverse of agreeableness), emotional stability (the obverse of neuroticism),and openness to experience; among women, with conscientiousness and openness to experience.Of the five traits, the evidence indicates that agreeableness had the greatest influence on genderdifferences in earnings: men were considerably more antagonistic (non-agreeable) than women,on average, and men alone were rewarded for that trait.
Keywords: J16; J31; 330; personality and wages; gender wage gap; Persönlichkeitspsychologie; Fraueneinkommen; Lohnstruktur; Schätzung; USA